'Irish & Roman Catholic Which Upsets All the People Here': Michael McDonnell and British Colonial Justice in Mandatory Palestine, 1927–1936. (23rd October 2017) - Davis, Simon
Abstract: In 1927 Michael McDonnell, a diasporic Irish Catholic, was appointed Mandatory Palestine's Chief Justice, being directed to institute firm British-style legal-judicial foundations for future self-governance. This entailed common, equal status for Arab and Jewish Palestinians, implicitly de-privileging the Jewish National Home. McDonnell was resisted in this by the British Mandate's Anglo-Jewish, pro-Zionist Attorney General, Norman Bentwich. McDonnell prevailed but only at the cost of being characterized lastingly as a pro-Arab, Catholic anti-Semite. McDonnell's continuing defence of a supreme, independent judiciary antagonized the Palestine Executive of High Commissioner Arthur Wauchope, who tried to co-opt rather than subordinate Zionist interests. Consequent frictions culminated in 1936 with McDonnell adjudicating against supra-legal British repression of Palestine's great Arab rebellion. For this he was dismissed and ostracized, subsequently publishing critiques of British policy in fringe right-wing organs. Yet McDonnell professed explicitly non-racist views, reflecting a liberal-minded, constitutional Irish nationalist equation of Palestine with Ireland, seeing comparable settler-colonial abuses and native distress as remediable only by transcendentally impartial justice. Britain reneging on these principles led McDonnell, like those Irish imperial servants noted in India, to identify with colonial subjects against colonialism. His case is one of empire as a system of domination being challenged from within, although his removal foreshadowed emerging imperial counter-insurgency's tendency not only to repress subject populations but deny civil-progressive alternatives for managing post-colonial transition.